Using corpora as authentic materials in the language learning classroom - Zhambylkyzy, M.; Yergalymkyzy, Y.Z.; Zauytbekovna, K.A. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The implementation of corpus linguistics (CL) to language teaching began in the late 1980s and early 1990s. A corpus-based approach to language teaching is becoming an important component in language learning classrooms. This article aims to discuss the role and effectiveness of corpora as a great methodological tool, to reveal the potential of corpus instruments, and to describe the ways of integrating corpora in teaching grammar and vocabulary as authentic material. Several examples are given about how corpus material can be used for different learning activities in the classroom and possible problems that a teacher may face are considered. This article defines the importance of learning a foreign language with the use of authentic materials and familiarizes readers with several methods of application corpora in the language learning environment. Finally, the survey questionnaire was conducted among teachers of various institutions in order to identify their awareness about corpus education. Results suggest that this questionnaire may be used to presume the future prospects for the application of the Corpus-based Method in Language Learning and Teaching.